Unveiling the layered structure of sulfobetaine polymer brushes through bimodal atomic force microscopy - Mondarte, Evan Angelo Quimada (2023)
Many zwitterionic polymer brushes exhibit highly stimuli-responsive properties stemming from the strong dipole and electrostatic interaction of their building blocks. Here, we showed how a combination of two atomic force microscopy (AFM) modes can reveal the layered structure of poly(sulfobetaine methacrylate) brushes synthesized by surface-initiated atom-transfer radical polymerization. Due to polydispersity and anti-polyelectrolyte effect, a diffused layer emerges on top of a condensed layer of the brush as a function of salt concentration. The amplitude-modulation mode of the AFM, owing to the tip’s dynamic motion, can only probe the more stable condensed layer near the substrate, whereas the force-spectroscopic mode with its high sensitivity can accurately detect the diffused layer and hence determine the total brush thickness. Infrared spectroscopy and quartz crystal microbalance monitoring revealed the strong ion-screening effect and higher brush hydration propensity of multivalent ions. Different cation valencies also showed subtle effects on the dimensionality of the layered structure. Our results highlight the usefulness of AFM in revealing various contextual phenomena that arise from the unique properties of zwitterionic polymers.